2003
DOI: 10.1016/s0022-2313(02)00572-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition on the spontaneous emission probabilities, stimulated emission cross-sections and local environment of Tm3+ in TeO2–WO3 glass

Abstract: Effect of composition on the structure, spontaneous and stimulated emission probabilities of various 1.0 mol% Tm 2 O 3 doped (1Àx)TeO 2 +(x)WO 3 glasses were investigated using Raman spectroscopy, ultraviolet-visible-nearinfrared (UV/VIS/NIR) absorption and luminescence measurements.Absorption measurements in the UV/VIS/NIR region were used to determine spontaneous emission probabilities for the 4f-4f transitions of Tm 3+ ions. Six absorption bands corresponding to the absorption of the 1 G 4 , 3 F 2 , 3 F 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…There exists a substantial amount of literature on the optical properties of Nd 3+ , Er 3+ , Tm 3+ and Yb 3+ doped tungsten-tellurite glasses [14][15][16][17][18][19][20]. However, apart from the study realized by ElMallawany and Abbas Ahmed [21] which reported the effect of Nd 3+ and Er 3+ on the glass transition temperature of tellurite based quaternary glasses, no studies exist about the effect of rare-earth elements on the thermal behavior of tellurite glasses in a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a substantial amount of literature on the optical properties of Nd 3+ , Er 3+ , Tm 3+ and Yb 3+ doped tungsten-tellurite glasses [14][15][16][17][18][19][20]. However, apart from the study realized by ElMallawany and Abbas Ahmed [21] which reported the effect of Nd 3+ and Er 3+ on the glass transition temperature of tellurite based quaternary glasses, no studies exist about the effect of rare-earth elements on the thermal behavior of tellurite glasses in a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Oxide glasses mainly include borate, phosphate, silicate, aluminate, germanate, tellurite, gallate and heavy metal oxide glasses. The last three kinds of glasses are seductive in recent years because their maximum phonon energies are believed to be the lowest in all of the oxide glasses, as a result, the nonradiative losses to the lattice will be smaller and the fluorescence quantum efficiencies of rare-earth ions will be higher [21][22][23][24][25]. In addition, the refractive indices of tellurite, gallate and heavy metal oxide glasses are higher than other oxide glasses and non-oxide glasses and it is beneficial in obtaining efficient radiative transitions in them.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, telluride glasses have numerous favorable optical properties such as: a wide transmission range from ultraviolet to mid-infrared (0.35-5.0 mm), lower phonon energy (700-750 cm À1 ) than other known glass hosts such as borates or silicates, high linear and nonlinear refractive index, good stability and resistance to moisture [1][2][3]. This has prompted a widespread interest in the spectroscopic investigation of Tm 3+ -doped telluride glasses [2][3][4][5][6][7][8][9][10]. In the particular case of TeO 2 -WO 3 glass host, researchers investigated the effects of glass composition on the emission strengths in thulium oxide (Tm 2 O 3 ) doped (1Àx)TeO 2 -(x)WO 3 glasses [7] and concluded, based on radiative lifetime calculations, that lower WO 3 content (x ¼ 0.15) favored the 1460 and 1800 nm emissions compared to the higher contents of x ¼ 0.…”
Section: Introductionmentioning
confidence: 99%